Golimumab effectiveness and safety in clinical practice for moderately active ulcerative colitis. Issue 9 (September 2018) - O'Connell, Jim; Rowan, Cathy; Stack, Roisin; Harkin, Grace; Parihar, Vikrant; Chan, Grace; Breslin, Niall; Cullen, Garret; Dunne, Cara; Egan, Laurence; Harewood, Gavin; Leyden, Jan; et al.
Abstract : Background and aims: Golimumab (GLB) is an antitumour necrosis factor-α (anti-TNF) therapy that has shown efficacy as induction and maintenance therapy for ulcerative colitis (UC). We aimed to describe the outcome of GLB therapy for UC in a real-world clinical practice. Patients and methods: Consecutive patients receiving GLB for UC in six Irish Academic Medical Centres were identified. The primary study endpoint was the 6-month corticosteroid-free remission rate. The secondary endpoints included the 3-month clinical response, time free of GLB discontinuation and adverse events. Results: Seventy-two patients were identified [57% men; median (range) age of 41.4 years (20.3–76.8); disease duration 6.6 years (0–29.9); follow-up 8.7 months (0.4–39.2)]. Sixty-four percent of patients were anti-TNF naive. The 3-month clinical response and the 6-month corticosteroid-free remission rates were 55 and 39%, respectively. Forty-four percent of patients discontinued GLB during the follow-up, median (95% confidence interval) time to GLB discontinuation 18.7 months (9.2–28.1). A C-reactive protein more than 5 mg/l at baseline was associated with failure to achieve 6-month corticosteroid-free remission and a shorter time to GLB discontinuation, odds ratio 0.2 (0.1–0.7), P =0.008, and hazard ratio (95% confidence interval) 2.8 (1.3–5.7), P =0.007, respectively. Adverse events occurred in 7% of patients ( n =5), all of which were minor and self-limiting. Conclusion: These real-world clinical data suggest that GLB is an effective and safe therapy for a UC cohort with significant previous anti-TNF exposure. An elevated baseline C-reactive protein, likely reflective of increased inflammatory burden, is associated with a reduced likelihood of a successful outcome of GLB therapy.